2161. Organism-Specific Turn Around Time Improvement in Urinary Specimens as a Result of Microbiological Laboratory Automation - Farooq, Nouman (Open Forum Infect Dis, 2019)
BACKGROUND: University Medical Center in Lubbock, TX is one of few medical centers using Becton Dickinson (BD) Kiestra Total Laboratory Automation (TLA) system since May 2015. The impact on organism-specific turn around time (TAT) in urinary specimens after implementation of TLA was evaluated. METHODS: After approval from the Quality Improvement Review Board, a retrospective analysis of microbiological data from urinary specimens in BD research database was performed. Before vs. after implementation (2013 vs. 2016) TAT was compared. Ten clinically relevant organisms were analyzed. Statistical analysis was performed with SAS software version 9.2. Data were analyzed using Chi-squared test. A P-value of < 0.05 was considered statistically significant. RESULTS: Overall, 2282 specimens from 2013 and 2306 specimens from 2016 were analyzed. Compared with before vs. after implementation of TLA, an overall improvement in TAT was observed (expressed as mean hours for each organism): Enterococcus faecalis (55.2 vs. 38.8), Enterococcus faecium (68.4 vs. 43.8), Escherichia coli (44.2 vs. 41.0), Klebsiella pneumoniae (45.0 vs. 44.0), Proteus mirabilis (44.8 vs. 38.6), Pseudomonas aeruginosa (58.9 vs. 37.7), Staphylococcus aureus (49.2 vs. 36.0), Streptococcus agalactiae (49.2 vs. 31.4), Streptococcus pneumoniae (51.7 vs. 61.8), Streptococcus pyogenes (62.6 vs. 26.6). It was also observed that improvement in TAT was more pronounced for Gram-positive organisms than Gram-negative organisms. P-value was < 0.01 for all organisms except Streptococcus pneumoniae (0.7985) and Streptococcus pyogenes (0.2562). The number of specimens with these two organisms was too small to be considered significant. CONCLUSION: Automation of microbiology laboratory leads to significant TAT improvement in urinary specimens, making early data availability to clinicians. This improves efficiency as well as supporting earlier antibiotic switch, antimicrobial stewardship and optimal patient care in treating urinary tract infections. DISCLOSURES: All authors: No reported disclosures.